SUCCESSFUL COMMUNICATION STRATEGIES IN GENDER SPEECH - Xoshimova , Nargis (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
The theory of indirect speech, which leads to successful communication, has been examined in contemporary works in pragmalinguistics. Especially the theory of implicitness and indirect meaning in the communication drew the attention of the world linguists. The aim of the present paper is to study the indirect meaning in gender speech in Uzbek, English and Russian languages. In conducting the successful communication the communicative strategies peculiar to Uzbek, English and Russian men and women have been revealed. The analytical and observation methods have been used in the study. As the result of the study it is found out that maintenance of the consecutive stages of felicity condition in the communication between a man and a woman promote the successful communication. The Uzbek people use implicit speech, which is characteristic both to women and men more than the English and Russian people. The use of implicit speeches by Uzbek people lead to effective communication. The use of imperative sentences by Uzbek men does not lead to communicative failure, but to successful communication. In the speech of Russian and English men, the imperative tone leads to misunderstanding and ineffective communication.